Neutralizing Cyber Attacks: Techniques of Neutralization and Willingness to Commit Cyber Attacks - Bossler, Adam M. (American journal of criminal justice, 2021)
Cyber attacks on critical infrastructure by ideology-based hackers may have both significant financial costs and public safety consequences. Scholars have been increasingly using Sykes and Matza’s (1957) techniques of neutralization to better understand the commission of various forms of cybercrime, including that of computer hacking. This study examines the effects of techniques of neutralization on college students’ willingness to commit cyber attacks, specifically defacing websites and compromising financial and government servers, against both domestic and foreign targets. An overall techniques of neutralization scale significantly predicted being willing to commit all examined forms of cyber attacks even after controlling for peer behavior, computer skills, time spent online, and being male. The strongest support was found for the techniques of condemnation of the condemners and claim of entitlement. The implications of the findings for our understanding of why certain individuals are more willing to commit cyber attacks and the situational crime prevention efforts to remove excuses for offenders are both explored.